Right atrial thrombus: A new cause of Paroxysmal complete Heart Block - Shimada, Shogo; Samuels, Louis (Journal of Cardiovascular Medicine and Cardiology, 2017)
We present a patient with a large right atrial (RA) thrombus complicated by paroxysmal complete atrioventricular (AV) block requiring urgent surgery. This is a rare complication of RA thrombi with the potential pathogenesis being direct mechanical insult on the AV node by the thrombus. Surgical thrombectomy led to complete resolution.